Die belang van Maleagi 1:2-5 vir die verstaan van die boek - Botha, A. J. (Verbum et ecclesia, 2000)
The importance of Malachi 1 :2-5 towards understanding of the Book Malachi In the past years scholarly attention to the book of Malachi has been scant. The outstanding feature in most of the studies is the fact that only certain themes from the book are used. The reason for doing this is mostly to justify certain viewpoints on matters such as divorce and the giving of tithes. As James Fischer aptly remarks: "They dissect him cleanly enough but leave him a cadaver" (1973:1177). The purpose of this article is to show that a meaningful understanding of the book is only possible once it is treated as a work of unity. This inner cohesion is already found in the first pericope (Mal 1:2-5) and functions as a paradigm towards an understanding of the remainder of the book. The outline with which the paradigm works, which is copied throughout the other pericopes, is that of past (1:2b-3), present (1:2a) and future (1:4-5). Within this outline the message of the whole book can be determined.